A qualitative study of old patients’ experiences of the quality of the health services in hospital and 30 days after hospitalization - Lilleheie, Ingvild (BMC Health Serv Res, 2020)
BACKGROUND: The number of people aged 80 years and above is projected to triple over the next 30 years. People in this age group normally have at least two chronic conditions. The impact of multimorbidity is often significantly greater than expected from the sum of the effects of each condition. The World Health Organization has indicated that healthcare systems must prepare for a change in the focus of clinical care for older people. The World Health Organization (WHO) defines healthcare quality as care that is effective, efficient, integrated, patient centered, equitable and safe. The degree to which healthcare quality can be defined as acceptable is determined by services’ ability to meet the needs of users and adapt to patients’ expectations and perceptions. METHOD: We took a phenomenological perspective to explore older patients’ subjective experiences and conducted semistructured individual interviews. Eighteen patients (aged from 82 to 100 years) were interviewed twice after discharge from hospital. The interview transcriptions were analyzed thematically. RESULTS: The patients found their meetings with the health service to be complex and demanding. They reported attempting to restore a sense of security and meaning in everyday life, balancing their own needs against external requirements. Five overarching themes emerged from the interviews: hospital stay and the person behind the diagnosis, poor communication and coordination, life after discharge, relationship with their next of kin, and organizational and systemic determinants. CONCLUSION: According to the WHO, to deliver quality healthcare, services must include all six of the dimensions listed above. Our findings show that they do not. Healthcare focused on measurable values and biomedical inquiries. Few opportunities for participation, scant information and suboptimal care coordination left the patients with a feeling of being in limbo, where they struggled to find balance in their everyday life. Further work must be done to ensure that integrated services are provided without a financial burden, centered on the needs and rights of older people.